Comparison of phenytoin and gold as second line drugs in rheumatoid arthritis. Issue 9 (September 1987) - Richards, I M; Fraser, S M; Hunter, J A; Capell, H A
Abstract : Phenytoin has known immunosuppressive properties, and a recent pilot study has indicated that it may have a second line effect in rheumatoid arthritis (RA). To evaluate this role 60 patients with active RA were randomly allocated to receive either oral phenytoin or intramuscular gold. The two treatment groups were comparable at the outset (Mann-Whitney U test). Twenty four patients completed 24 weeks of therapy in each group and no unexpected side effects were encountered. All variables except haemoglobin (Hb) improved significantly in the gold group while in the phenytoin group significant improvement was limited to articular index, erythrocyte sedimentation rate (ESR), and Hb. Between group comparison (Mann-Whitney) at week 24 showed a significant advantage of gold over phenytoin for pain score and morning stiffness. Thus phenytoin appears to exert a less potent second line effect than gold and is unusual in influencing laboratory indicators of disease activity more than clinical variables. This is likely to limit its usefulness as a second line drug in RA.